Avaliação ergonômica de uma órtese ativa de punho para a reabilitação da rigidez em pessoas com a doença de Parkinson - Costa, Samila Carolina (2020)
Introduction: Parkinson's disease (PD) is a chronic and progressive disease that presents characteristic motor symptoms. Rigidity is one of the main motor symptoms of PD and can manifest itself in different areas of the body, being more common in the upper limbs, which makes it difficult to perform activities that involve the use of hands. Therefore, physical therapy rehabilitation is extremely important for maintaining the functionality of the limbs affected by PD motor symptoms, influencing the quality of life of individuals affected by the disease. In this sense, the use of robotic devices in the rehabilitation of motor symptoms of Parkinson's disease is an area in increasing expansion. Objective: To evaluate the ergonomics of an active wrist orthosis developed for the rehabilitation of symptoms of rigidity in individuals with PD. Methods: The muscle activity of the carpal flexors and extensors was estimated using electromyography. To estimate the motion amplitude (MA), a biomechanical model of the upper body was developed in the Visual3D software and the MA of wrist flexion and extension was estimated. Both characteristics, EMG and MA, were evaluated with and without the use of the active wrist orthosis and later compared using statistical methods to verify the influence of the active wrist orthosis. Results: The results show that the use of the orthosis mainly influences the wrist extension. For the wrist extension movement, it was observed an average increase of 22% in the muscular activity of the long radial carpal extensor and an average decrease of 9º in the motion amplitude of the wrist extension when using the orthosis. Conclusion: The changes in electromyographic activity and motion amplitude caused by the use of the evaluated active wrist orthosis are not significant in the sense that the device does not impose a significant limitation of joint amplitude in a clinical application, and the increase in muscle activity does not interfere in performing the tasks proposed in the experimental protocol, confirming the ergonomic design of the orthosis and the potential to be used in the rehabilitation of the wrist of individuals affected by Parkinson's disease in a clinical setting.